The Nature and Timing of Specific Copy Number Changes in the Course of Molecular Progression in Diffuse Gliomas: Further Elucidation of Their Genetic “Life Story” - Jeuken, Judith W.M. (Brain Pathol, 2010)
Up till now, typing and grading of diffuse gliomas is based on histopathological features. However, more objective tools are needed to improve reliable assessment of their biological behavior. We evaluated 331 diffuse gliomas for copy number changes involving 1p, 19q, CDKN2A, PTEN and EGFR(vIII) by Multiplex Ligation‐dependent Probe Amplification (MLPA®, Amsterdam, The Netherlands). Specifically based on the co‐occurrence of these aberrations we built a model for the timing of the different events and their exact nature (hemi‐ → homozygous loss; low‐level gain → (high‐copy) amplification) in the course of molecular progression. The mutation status of IDH1 and TP53 was also evaluated and shown to correlate with the level of molecular progression. The relevance of the proposed model was confirmed by analysis of 36 sets of gliomas and their 39 recurrence(s) whereas survival analysis for anaplastic gliomas confirmed the actual prognostic relevance of detecting molecular malignancy. Moreover, based on our results, molecular diagnostic analysis of 1p/19q can be further improved as different aberrations were identified, some of them being indicative for advanced molecular malignancy rather than for favorable tumor behavior. In conclusion, identification of molecular malignancy as proposed will aid in establishing a risk profile for individual patients and thereby in therapeutic decision making.